Sensibilização à dor no equilíbrio postural dinâmico em pacientes com osteoartrite de joelho - Silva, Marialice Gyaraki da (Universidade Federal de São Carlos, 2024)
Knee osteoarthritis (KOA) is a common and disabling condition characterized by several structural changes, wherein the main complaint of these individuals is pain, as well as a decrease in functional capacity and balance, factors that can affect their motor responses and postural control. In this study, the primary objective was to analyze the influence of pain sensitization on the postural balance of subjects with KOA, and to explore the relationship between catastrophizing, kinesiophobia, and physical functionality as a secondary objective. This study was a cross-sectional, exploratory, quantitative model. For the study, 52 subjects with a clinical diagnosis of KOA were recruited. All subjects were evaluated by quantitative sensory tests (TSQ) to quantify central pain sensitization measures. The Western Ontario and McMaster University (WOMAC) Tampa questionnaires for Kinesiophobia, Pain Catastrophizing, and physical capacity tests (sitting and standing, stairs, and 40m performance) were also applied. For postural balance measurements, the modified Star Excursion Balance Test (SEBT) was applied in three directions. For data analysis, a descriptive analysis of the variables was carried out, and the normality of the data was verified using the Kolmogorov-Smirnov test. The multiple linear regression model was used to determine the association between the study variables. For all analyses, a significance level of 5% (p<0.05) was adopted. Results: Pain sensitivity measures were not able to predict performance on the SEBT test. On the other hand, it was observed that measures associated with physical fitness, notably the 30-second chair stand-up and sit-down test and the physical activity component of the WOMAC questionnaire, proved to be better indicators of performance in the SEBT test in individuals with knee osteoarthritis.
Pain sensitization in dynamic postural balance among patients with knee osteoarthritis
Keywords: Osteoartrite de joelho; Dor crônica; Equilíbrio postural; Knee osteoarthritis; Chronic pain; Postural balance; CIENCIAS DA SAUDE